Bactericidal Activity of Vancomycin in Cerebrospinal Fluid - Nagl, Markus (American Society for Microbiology, 1999)
Intraventricular application of vancomycin is an effective therapeutic regimen for the treatment of shunt-associated staphylococcal ventriculitis. We examined the in vitro activity of vancomycin at high concentrations against Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis ATCC 12228 in human cerebrospinal fluid samples. Time-kill curves revealed equal efficacies for concentrations of 10, 100, and 300 μg/ml, and incubation times of 24 to 48 h were needed to achieve a 3 log(10) reduction of viable bacteria. A concentration of 5 μg/ml showed a slightly lower activity, but this difference was not significant. In an infant who was successfully treated for shunt-associated ventriculitis due to S. epidermidis by once-daily local administration of vancomycin (3 mg for 2 days and 5 mg for 4 days [0.5 to 0.8 mg/kg of body weight]) the in vivo kill kinetics were similar to those for the in vitro results. These results support time-dose regimens that provide trough vancomycin levels of 5 to 10 μg/ml.